Difference between revisions of "009A Sample Final A, Problem 4"
Jump to navigation
Jump to search
(Created page with "<br> <span style="font-size:135%"><font face=Times Roman> 4. Find an equation for the tangent line to the function <math style="vertical-align: -13%;">-x^{3}-2xy+y^{3}=-...") |
m |
||
(11 intermediate revisions by the same user not shown) | |||
Line 8: | Line 8: | ||
! Foundations: | ! Foundations: | ||
|- | |- | ||
− | |Since only two variables are present, we are going to differentiate everything with respect to | + | |Since only two variables are present, we are going to differentiate everything with respect to <math style="vertical-align: 0%">x</math> in order to find an expression for the slope, <math style="vertical-align: -21%">m = y' = dy/dx</math>. Then we can use the point-slope equation form <math style="vertical-align: -21%;">y-y_{1} = m(x-x_{1})</math> at the point <math style="vertical-align: -21%">\left(x_1,y_1\right) = (1,1)</math> to find the equation of the tangent line. |
|- | |- | ||
− | |Note that implicit differentiation will require the product rule <u>''and''</u> the chain rule. In particular, differentiating | + | |Note that implicit differentiation will require the product rule <u>''and''</u> the chain rule. In particular, differentiating <math style="vertical-align: -18%">2xy</math> can be treated as |
|- | |- | ||
| <math>(2x)\cdot (y),</math> | | <math>(2x)\cdot (y),</math> | ||
Line 16: | Line 16: | ||
|which has as a derivative | |which has as a derivative | ||
|- | |- | ||
− | | <math>2\cdot y+2x\cdot y' = 2y +2x\cdot y'.</math> | + | | <math>2\cdot y+2x\cdot y' = 2y +2x\cdot y'.</math><br> |
|} | |} | ||
+ | |||
+ | '''Solution:''' | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
Line 24: | Line 26: | ||
|We use implicit differentiation on our original equation to find | |We use implicit differentiation on our original equation to find | ||
|- | |- | ||
− | | | + | | <math>-3x^{2}-2y-2x\cdot y'+3y^{2}\cdot y'=0.</math> |
|- | |- | ||
− | | | + | |From here, I would immediately plug in <math style="vertical-align: -22%">(1,1)</math> to find <math style="vertical-align: -22%">y'</math>: |
|- | |- | ||
− | | | + | | <math style="vertical-align: -20%">-3-2-2y'+3y'=0</math>, or <math style="vertical-align: -20%">y' = 5.</math><br> |
|} | |} | ||
Line 34: | Line 36: | ||
!Writing the Equation of the Tangent Line: | !Writing the Equation of the Tangent Line: | ||
|- | |- | ||
− | |Now, we simply plug our values of | + | |Now, we simply plug our values of <math style="vertical-align: -17%">x = y = 1</math> and <math style="vertical-align: 0%">m = 5</math>  into the point-slope form to find the tangent line through <math style="vertical-align: -20%">(1,1)</math> is |
+ | |- | ||
+ | | <math>y-1=5(x-1),</math> | ||
+ | |- | ||
+ | |or in slope-intercept form | ||
+ | |- | ||
+ | | <math>y=5x-4.</math><br> | ||
|} | |} | ||
[[009A_Sample_Final_A|'''<u>Return to Sample Exam</u>''']] | [[009A_Sample_Final_A|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 18:23, 27 March 2015
4. Find an equation for the tangent
line to the function at the point .
Foundations: |
---|
Since only two variables are present, we are going to differentiate everything with respect to in order to find an expression for the slope, . Then we can use the point-slope equation form at the point to find the equation of the tangent line. |
Note that implicit differentiation will require the product rule and the chain rule. In particular, differentiating can be treated as |
which has as a derivative |
|
Solution:
Finding the slope: |
---|
We use implicit differentiation on our original equation to find |
From here, I would immediately plug in to find : |
, or |
Writing the Equation of the Tangent Line: |
---|
Now, we simply plug our values of and into the point-slope form to find the tangent line through is |
or in slope-intercept form |
|